A structural equation model of the family physicians attitude towards their role in prevention: a cross-sectional study in Switzerland. (26th June 2018) - Cohidon, Christine; Wild, Pascal; Senn, Nicolas
Abstract: Background: In contrast to many studies exploring barriers to preventive care in family medicine, there is less quantitative research regarding the self-perceived role of family physicians (FPs) in prevention and its predictive factors. Moreover, the existing studies considered this attitude as a homogeneous entity. The objective of this study is firstly, to characterize FPs' attitudes towards prevention taking into account nine different prevention themes, and secondly, to explore the factors that could be predictive of this attitude. Methods: The data stem from a cross-sectional national survey on prevention we conducted in Switzerland from 2015 to 2016 (170 physicians randomly drawn, online questionnaire). We first performed a confirmatory factor analysis to define a homogeneous latent variable regarding physicians' attitude towards prevention, then, a structural equation modeling to identify potential predictors. Results: The FP' attitude towards their role in preventive care was homogeneously positive whatever the topic (smoking, drinking dietary habits, physical activities, and more generally, cardiovascular risk factors) except for occupational risks and cannabis consumption. A feeling of good effectiveness was a positive predictor of this positive attitude while seniority, the lack of reimbursement and being a physician from the German-speaking area were negative predictors. Conclusion: The FP' attitude about their role in prevention is homogeneous concerning the 'classical' topics of prevention, whereas they still under-recognize certain topics as important fields for prevention. To change this situation, we probably need a global effort to introduce other ways of thinking about prevention, including not only FP but also all stakeholders.